The Spatiality of the Body in Football - Nunes, Nuno André; Petiot, Grégory Hallé; Adeosun, Kola (Advances in Social Sciences Research Journal, 2024)
This research aims to address the critical issue of how the spatiality of the body intersects with football philosophy, with a specific focus on the context of training and match strategies. Traditionally, in football, coaching factors emerge within the training environment and are closely aligned with the intended game model. However, isolating these factors from the broader game model risks decontextualizing them, potentially undermining crucial aspects such as solidarity, team spirit, motivation, discipline, and rigor. Moreover, there is a pressing need to ensure that physical, technical, and psychological aspects are subordinated to tactical thinking and a relentless pursuit of victory during training sessions. This imposes a mindset of seriousness and rigor to effectively navigate the demands of complexity inherent in collective play. Drawing insights from philosophical discussions by Merleau-Ponty and Edgar Morin, as well as contributions from Manuel Sérgio and other scholars, this research seeks to deepen our understanding of the intricate relationships between players within a team. By exploring these dynamics, the study aims to shed light on how interactions among players shape team dynamics and influence individual players’ perceptions within the broader coaching context. Ultimately, the paper endeavours to contribute to a nuanced comprehension of the spatial and philosophical dimensions inherent in football training processes, thus offering valuable insights for both researchers and practitioners in the field.